Determination of long-term investment intentions: Moderating role of construal priming - Arief Kusuma Among Praja; Suryanti Takarinawati; Obsatar Sinaga (Contemporary Economics, 2020)
The current study investigates long-term investment intentions by linking the moderating role of construal priming in the causal relationship to defensive pessimism, which is a novel approach. The data was collected from 450 employees of private institutions by means of questionnaires and PLS-SEM was used in analysis. The results indicated a positive relationship between defensive pessimism, self-control, consumer financial product bias, and long-term investment. In addition, negative moderation role of the level of construal priming was observed, along with the links of defensive pessimism and long-term investment. Thus, the study provides crucial contexts for understanding long-term investment intentions from a behavioral perspective, which is often ignored in the financial management literature.
Keywords: G41; G51; 330; Level of construal priming; defensive pessimism; long-term investment; consumer financial product bias